THE INFLUENCE OF COOPERATIVE LANGUAGE LEARNING TECHNIQUE (CLLT), LEARNING MOTIVATION TOWARDS THE TWEFLTH GRADE STUDENTS’ READING COMPREHENSION ACHIEVEMENT ON NARRATIVE TEXTS AT SMA NEGERI 2 SEMBAWA - Lasmaida Naomi Saragi (Universitas PGRI Palembang, 2019)
AbstractThis research is concerned with the influence of cooperative language learning technique and reading comprehension achievement on narrative text of SMA Negeri 2 Sembawa. In this study 64 students of twelfth grade students of SMA Negeri 2 Sembawa in the academic year 2017/2018 were chosen as sample by two stage random sampling. This study applied factorial research design. The data were collected by using questionnaire and t-test. The data were analyzed by using Paired Sample t-test, Independent sample t-test and Two Ways Anova. The result, there was is a significant difference in reading comprehension achievement between the students who have high learning motivation and those who have low learning motivation taught by cooperative language learning technique (CLLT). Conclusion suggest that there was a significant influence of cooperative language learning technique and learning motivation of the twelfth grade students’ reading comprehension achievement on narrative text of SMA Negeri 2 Sembawa.Keywords:Cooperative Language Learning Technique (CLLT), Learning Motivation, Reading Comprehension Achievement